Conference – 1992 Equation (3)

P = f ( P t 1 , L ) , where f 1 > 0 , f 2 > 0 MathType@MTEF@5@5@+= feaagKart1ev2aaatCvAUfeBSjuyZL2yd9gzLbvyNv2CaerbuLwBLn hiov2DGi1BTfMBaeXatLxBI9gBaerbd9wDYLwzYbItLDharqqtubsr 4rNCHbGeaGqiVu0Je9sqqrpepC0xbbL8F4rqqrFfpeea0xe9Lq=Jc9 vqaqpepm0xbba9pwe9Q8fs0=yqaqpepae9pg0FirpepeKkFr0xfr=x fr=xb9adbaqaaeGaciGaaiaabeqaamaabaabaaGcbaGaaeiuaiabg2 da9iaabAgadaqadaqaaiaabcfadaWgaaWcbaGaaeiDaiabgkHiTiaa igdaaeqaaOGaaiilaiaabYeaaiaawIcacaGLPaaacaGGSaGaae4Dai aabIgacaqGLbGaaeOCaiaabwgacaaMc8UaaeOzamaaBaaaleaacaaI Xaaabeaakiabg6da+iaaicdacaGGSaGaaeOzamaaBaaaleaacaaIYa aabeaakiabg6da+iaaicdaaaa@4E36@